Prevalence and predictors of atypical histology in endometrial polyps removed by hysteroscopy: A secondary analysis from the SICMIG hysteroscopy trial (Facts Views Vis Obgyn, 2019)
BACKGROUND: The aim of this study is to assess the prevalence of atypical hyperplasia (AH) and endometrial cancer (EC) within endometrial polyps (EPs) removed by hysteroscopy. METHODS: Hysteroscopic polypectomy interventions were performed over 1436 consecutive patients with Eps to complete a prospective observational trial (Canadian Task Force Classification II-2) including 19 Italian Gynecologic Departments (University-Affiliated or Public Hospitals) for a secondary multicenter analysis. RESULTS: At histological analysis, in 1404 patients (97.8%) EPs were classified as benign, whereas in 32 patients (2.2%) EPs were diagnosed as atypical (i.e. with AH or EC). Specifically, AH and EC were found in 17 (1.2%) and 15 (1.0%) cases, respectively. Risk factor analysis showed that menopausal status, BMI and size of EPs were associated with increased risk of atypical EPs (p<0.0001). Abnormal uterine bleeding, EPs number, contraceptive therapy and tamoxifen were not associated with increased risk of atypia (p=ns). The cut-off points for increased risk of atypical polyps were 54.2 years old, BMI of 25.3 and EP size of 2.2 cm. Hysterectomy specimens were analyzed in 21 women with atypical EPs, showing the concomitant presence of atypical tissue in non-polypoid endometrium in the majority of patients (n=14 women, 66.6%). CONCLUSION: The prevalence of endometrial cancer and atypical hyperplasia in endometrial polyps is low, although it is increased in women who are overweight, older than 54 years of age or with a polyp larger than 2cm.